The Influence of Discipline, Knowledge Management and Competence on The Performance of Outsourcing Employees - Sulvia Sabtu; Hendri Tanjung; Amir Teungku Ramly (Universitas Mercu Buana, 2023)
Performance management is management about creating relationships and ensuring effective communication between employees and their superiors. This study aims to analyze the influence of discipline, knowledge management and competence on the performance of outsourced employees at Plasa Telkom Bogor Bogor Regional 2. This research uses quantitative research with a descriptive approach. The sampling method used in this study was simple random sampling. The number of samples to be used in this study were 30 outsourced employees. The results showed that all variables had a significant effect on variable Y. The work discipline variable (X1) had a significant effect on employee performance because the results of the t significance test showed that the sig value of X1 was 0.036, this shows a significance value of less than 0.05. The Knowledge Management variable (X2) has a significant effect on Employee Performance (Y), this can be seen from the t significance test which shows the sig value of X2 is 0.035 (smaller than 0.05). Competency variable (X3) has a significant effect on employee performance (Y), this can be seen from the t significance test which shows the sig value of X3 is 0.015 (smaller than 0.05).